Teething and nutritional condition in children between 5 and 13 years. - Clotilde de la Caridad Mora Pérez; Raúl López Fernández; Juan J. Apolinaire Pennini (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: During last decades it has become increasingly evident the importance of nutritional factors in the development and renovation of buccal tissues, particularly of teeth. Objective: To characterize permanent teething and its relation with nutritional factors in children between 5 and 13 years. Methods: Cross-sectional descriptive, observational study developed in a universe formed by 1003 children of Health Area II in Cienfuegos, out of which a sample of 330 children was selected. Data was collected from schools, regarding the teething age and nutritional status. Ponder and measurements were carried out. Results: The average teething age was lower for girls in both maxillary bones; teething sequence was 6,1,2,4,5,3,7 for the maxilla and 6,1,2,3,4,5,7 for the inferior maxillary bone. There was a prevalence of normal weight among girls, followed by thin and undernourished values. Among boy, there was a prevalence of obesity, overweight and normal weight in that order. Nutritional statuses of thin and undernourished were related with a delayed teething, mainly in the inferior maxillary bone. Permanent teething was delayed with regard to the national media. Conclusion: A clear relation was established between teething age and nutrition, mainly among thin and undernourished children.